2020
DOI: 10.1007/s00339-020-03711-2
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of structural and optical properties of ZnO bulk crystals and polycrystalline films grown by sol-gel method

Abstract: The presented article concerns the comparison between two different zinc-oxide structures - bulk crystals and polycrystalline thin films. Bulk crystals were grown by a Bridgman method. For thin-film production, a sol-gel spin-coated method was chosen. A part of thin layers samples was annealed in 600 $$^{o}$$ o C to induce recrystallization. The morphological and structural properties of all samples were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…The frequencies of the silent B1 (low) and B1 (high) modes have been calculated as 260 and 540 cm1, respectively. [ 42,43 ] In general, the silent B1 mode is inactive in the perfect crystalline ZnO bulk structure. This mode is related to the phonon vibrations of ZnO and can be activated in a disordered structure.…”
Section: Resultsmentioning
confidence: 99%
“…The frequencies of the silent B1 (low) and B1 (high) modes have been calculated as 260 and 540 cm1, respectively. [ 42,43 ] In general, the silent B1 mode is inactive in the perfect crystalline ZnO bulk structure. This mode is related to the phonon vibrations of ZnO and can be activated in a disordered structure.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectra shows typical bands corresponding to C plane of bulk ZnO. [ 24 ] Fingerprint of BSA could not be detected, most likely due to very small thickness of the adsorbed layer as shown by atomic force microscopy (AFM) measurements. Spectroscopy of such thin layers of biomolecules is extremely challenging.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that E1 mode does not appear for ZnO thin film, favoring the growth of ZnO thin film along c-axis. The peak observed at 1110 cm -1 and 2890 cm -1 corresponds to A1 (2LO) mode and organic residue (CH3 stretching), (does not decompose completely) respectively [60].…”
Section: Fig 11 Rt Raman Spectra Of Zno Thin Filmmentioning
confidence: 98%